The false spider mites of the genera Aegyptobia Sayed and Phytoptipalpus Trägårdh (Acari: Tenuipalpidae) from Iran - Khanjani, Masoumeh; Khanjani, Mohammad; Seeman, Owen D. (Zootaxa, 2012)
Two new species of the genus Aegyptobia Sayed and 1 new species of Phytoptipalpus Trägårdh are described from Iran:A. bromi sp. nov. from Bromus tectorum (Poaceae); A. nazarii sp. nov. from Poa bulbosa L. (Poaceae); and P.kurdistaniensis sp. nov. from wild rose bushes, Rosa woodsii (Rosaceae). This is the first record of Phytoptipalpus fromIran. We also redescribe Aegyptobia beglarovi Livschitz and Mitrofanov, 1967, A. persciae Khorowshahi and Arbabi,1997, A. tragardhi Sayed, 1950, and A. salicicola Al-Gboory, 1987; the latter species has only 2 anal setae and is thusmoved to Phytoptipalpus. Aegyptobia kharazii Mesa and Moraes, 2009 syn. nov. is regarded as a junior synonym ofAegyptobia beglarovi Livschitz and Mitrofanov, 1967; Aegyptobia ueckermanni Khorowshahi and Arbabi, 1997 syn. nov.is regarded as a junior synonym of Aegyptobia tragardhi Sayed, 1950; Aegyptobia daneshvari Parsi and Khosrowshahi,1990 syn. nov. is regarded as a junior synonym of Phytoptipalpus salicicola (Al-Gboory, 1987). A key to all known Iranian species of the genus Aegyptobia is provided.